A Study on Providing the Laboratory N°. 9 at University of El Oued using Photovoltaic Energy - Aymen Touati Brahim; Abdou Djamel Abd Nacer; Ghrib Elmouldi (University of Shahid Hama Lakhdar - El Oued, 2024)
Energy is one of the most essential and essential elements of life, as demand for it continues to increase, it has become necessary to seek alternative sources of production through the exploitation of renewable energies. One of the most important sources is the use of solar energy because of its many advantages. In this thesis, we did a theoretical study on the solar power supply of Laboratory No. 9 of the Department of Electrical Engineering – Faculty of Technology- at the University of El Oued, and we did a simulation of the solar panel system by MATLAB/SIMULINK which enabled us to observe and study the photovoltaic system.تعد الطاقة من أهم العناصر الأساسية والضرورية للحياة، نظرا للزيادة المستمرة في الطلب عليها ، فقد أصبح من الضروري البحث عن مصادر بديلة لإنتاجها وذلك من خلال استغلال الطاقات المتجددة ومن أهم المصادر استعمالا الطاقة الشمسية بسبب مزاياها العديدة. في هذه الأطروحة، قمنا بعمل دراسة نظرية حول تزويد المخبر رقم 9 التابع لقسم الهندسة الكهربائية بكلية التكنولوجيا بجامعة الذي مكننا من مراقبة MATLAB/SIMULINK الوادي بالطاقة الشمسية وقمنا بعمل محاكاة لنظام الألواح الشمسية بواسطة النظام الكهروضوئي ودراسته.
Master's theses: specializing Electrical control
Keywords: Photovoltaic; boost Converter; MPPT; Modeling; Simulation; الخلايا الكهروضوئية، محول التعزيز، MPPT، النمذجة، المحاكاة